Quality Evaluation On Rotary Ultrasonic Assisted Drilling For Chemically Strengthened Glass - Raja Abdullah, Raja Izamshah; Kasim, Mohd Shahir; Lamat, Arshad; Rosman, Muhammad Rafiq; Kasman, Muhammad Zaki; Liew, Pay Jun; Abdul Aziz, Mohd Sanusi; Raja Abdullah, Raja Syamsul Azmir (Penerbit UniMAP, 2021)
Demand for Chemically Strengthened (CS) glass has steadily increased for the past decade predominantly by the electronic devices industry. One of the major reasons are due to its superior strength and crack resistance properties. However, due to its superior properties which resistant to compressive loads causing drawback to the subsequent secondary manufacturing process i.e. hole drilling. Conventional drilling process towards this glass tends to generate high tensile thrust that consequently affect the hole performances and accuracy. Considering these facts, in this paper a new drilling technique which assisted by the ultrasonic vibration frequency known as Rotary Ultrasonic Assisted Drilling (RUAD) is propose aim to increase the hole quality. A set of experimental work was conducted in order to assess the effects of the RUAD parameter namely cutting speed, feed rate, ultrasonic frequency and vibration amplitude towards hole quality. The analytical results demonstrated that the presence of the intermittent ultrasonic vibration amplitude was able to minimize the chipping area and enhance the hole quality with acceptable tolerance value.